VaD - An Integrated Framework for Cognitive Rehabilitation - Balea, Maria; Muresanu, Dafin; Alvarez, Anton; Homberg, Volker; Bajenaru, Ovidiu; Guekht, Alla; Heiss, Wolf-Dieter; Popa, Livia; Vester, Johannes; Muresanu, Ioana; Birle, Codruta; Slavoaca, Dana (CNS & Neurological Disorders - Drug Targets, 2018)
Background & Objective: Vascular dementia is the second most common cause of dementia, with clinical features that depend on neural substrates affected by the vascular lesions. Like most neurological disorders, it involves alterations that range from the molecular level to neuronal networks. Such alterations begin as compensatory mechanisms that reshape every subsystem involved in the brain's homeostasis. Although there have been recent huge advances in understanding the pathophysiology of cognitive dysfunction, a suitable therapeutic approach to vascular dementia remains elusive. Pharmacological interventions have failed to sustainably improve cognitive function, and it is a well-known fact that there is a need to change the current view for providing neuroprotection and enhancing neurorecovery after stroke. Studies regarding cognitive training are also faced with the difficulty of drawing up protocols that can embrace a holistic approach in cognitively impaired patients. Conclusion: This review will present a brief synthesis of current results from basic research data and clinical studies regarding pharmacological and non-pharmacological interventions in vascular dementia and will offer an integrated view from the perspective of systems biology.
Keywords: cognitive neurorehabilitation